Talons of power - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2018)
With the return of dangerous old dragon Darkstalker, Turtle wants to hide his powers--even if they could help. But when Turtle's friends seem convinced Darkstalker has changed for the better, Turtle knows better, and he might have to call on his secret abilities to save them all.